Bioethics North and South: Creating a common ground - Miles, S.H.; Laar, A.K. (Ethics, Medicine and Public Health, 2018)
Bioethics as practiced in Europe, the United States, and Canada has a tenuous and tentative reach into the developing countries of Africa, South America, and Asia. This paper explores the problematic translation of bioethics between the Global North and South; and between resource rich and resource poor countries. As Alexander Capron put it in 2007, bioethics has a 10/90 problem, analogizing to the observation that medical research spends 90% of its resources on problems affecting 10% of the world's population. Today, UNESCO's bioethics website says bioethics focuses on “stem cell research, genetic testing, cloning, progress in the life sciences”. Any review of the most widely cited bioethics articles and journals finds that the writing is largely centered within an enclave of first world concerns. Stem cells and cloning are neither health care nor health science priorities of developing countries. The priorities of developing countries (i.e., those that would improve the health of populations or that refer to local diseases) are marginalized. Costly and/or impractical medical infrastructure is discussed or proposed. The first-world orientation of bioethics was perhaps somewhat practicable during a post-World War II stasis, but it is increasingly dysfunctional and even dangerous in the context of twenty-first century climate change, refugee movements, and disease vector migrations. A new global bioethics is urgently needed.
Bioéthique nord et sud : créer un terrain commun
Keywords: Africa; Bioethics; Developing countries; Ethics; Human rights; Medical; Principles; Public health; South America